Economic feasibility analysis of rock-basalt dust for soybean production in the Dourados/MS - Almeida, Risely Ferraz; Gomes, Willian Lange (Scientia Agraria Paranaensis, 2022)
With the hypothesis that the use of rock dust is an economically viable alternative for supplementary fertilization in the soybean crop in the region of Dourados, Mato Grosso do Sul (MS), this study evaluated the use of rock dust in the soybean crop, taking into account the relationship between productivity and cost of production. The experiment was installed with the application of rock dust (0, 2.5, 5.0, 7.5, and 10 Mg ha-1) in soybean cultivation. Productivity, production cost, and economic viability indicators were monitored and calculated. Results showed that the application of rock dust positively influenced the total revenue, as well as the gross margin and net margin of the treatments, allowing a higher rate of return on the producer's investments. With the application of doses greater than 2.5 Mg ha-1 of rock dust, a higher total revenue could be obtained, however, there was a lower value of gross margin, net margin, leveling price, and leveling point components. Therefore, conclude that the application of up to 2.5 Mg ha-1 is a viable alternative to increase soybean profitability in the region of Dourados/MS.